The value of tumor-stroma ratio as predictor of pathologic response after neoadjuvant chemoradiotherapy in esophageal cancer. (January 2020) - van Pelt, G.W.; Krol, J.A.; Lips, I.M.; Peters, F.P.; van Klaveren, D.; Boonstra, J.J.; de Steur, W.O.; Tollenaar, R.A.E.M.; Farina Sarasqueta, A.; Mesker, W.E.; Slingerland, M.
Highlights: Scoring the tumor-stroma ratio is a simple and reproducible method. Tumor-stroma ratio and response to neoadjuvant chemoradiotherapy are correlated. Stroma-low tumors are likely to respond better to neoadjuvant chemoradiotherapy. Abstract: Background and purpose: With currently available techniques, the prediction of pathologic complete response after neoadjuvant chemoradiotherapy is insufficient. The tumor-stroma ratio (TSR) has proven to be a predictor of survival for several types of cancer, including esophageal. The aim of this study was to investigate the value of TSR in predicting pathologic response after neoadjuvant chemoradiotherapy in esophageal cancer patients. Materials and methods: Patients with esophageal adenocarcinoma or squamous cell carcinoma who received neoadjuvant chemoradiotherapy followed by a resection were selected. Haematoxylin and eosin (H&E) stained sections of diagnostic biopsies were collected and TSR was independently assessed by two investigators. Patients were categorized in stroma-low (≤50% stroma) and stroma-high (>50% stroma) groups for further analyses. The tumor regression grade (TRG) was assessed on H&E stained sections of the resected primary tumor to determine pathologic response. Results: A total of 94 patients were included in this study, of which 76 patients were categorized as stroma-low and 18 as stroma-high. Forty-two (45%) patients had a major pathologic response (TRG 1–2), whereas 52 (55%) were considered non-responders. After adjustment for gender, tumor type, cT-status and differentiation grade, patients with a stroma-high tumor showed a higher chance of no response compared to patients with a stroma-low tumor (OR 3.57, 95%CI 1.03–12.31, P  = 0.04). Conclusion: TSR showed to have the potential to aid in the prediction of pathologic response in esophageal cancer patients receiving neoadjuvant chemoradiotherapy. Larger validation studies are necessary before implementing this method in daily practice.